Transitivity Analysis in Allende's 'And of Clay Are We Created': Language, Emotion, and Social Commentary - Jesudas, Roseline (English Lecturers and Teachers Association (ELTA), 2025)
This study investigates the transitivity processes in Isabel Allende's short story “And of Clay Are We Created,” employing Halliday's systemic-functional theory, particularly focusing on the ideational metafunction. This framework enables an exploration of how language reflects experiences and ideologies within the short story. By scrutinizing transitivity, the analysis reveals Allende's expression of emotional depth and societal critique, shedding light on her characters' motivations and perspectives. Utilizing qualitative content analysis, the research aims to uncover the nuanced interplay between language and meaning in the text, highlighting how Allende's narrative fosters a critical understanding of societal issues. The findings are anticipated to enhance the discourse surrounding the intricate relationship between language, narrative identity, and social commentary in contemporary literature, illustrating how linguistic choices resonate within broader ideological contexts. Ultimately, this study contributes to an enriched appreciation of Allende's literary artistry and its socio-cultural implications.